Survei Program Latihan Ekstrakurikuler Dan Sarana Prasarana Terhadap Pencapaian Prestasi Olahraga Bola Basket Di Sekolah Menengah Atas Negeri Se-Kabupaten Purworejo (Universitas Negeri Semarang, 2020)
The purpose .of this .research is to get to know how the availability of the Training Program and Facilities that were Used in the Extracurricular of Basketball in State Senior High Schools in Kabupaten Purworejo Toward the Achievement. This study aimed to determine the basketball extracurricular training program and facilities in each state high school in Kabupaten Purworejo toward the achievement of basketball. This research belonged to a qualitative descriptive study using survey methods with .data collection techniques applied observation, interviews, documentation, and questionnaires. The study was conducted from February 15, 2020 until March 15, 2020. The subjects in this study were basketball extracurricular trainers or coach in state high schools in kabupaten Purworejo. Data analysis applied data reduction, . data display, and conclusion drawing / verification. The results of this study indicated that the basketball extracurricular training programs were already applied by every school. But, the completeness of the training programs were being the problems. There were 4 schools that have complete training programs and there were 4 schools that have incomplete training programs. For the entire facilities had been supported by each school. But, for the quantity, there were some schools that still lack of facilities that can be used to run the basketball extracurricular training activities. Based .on the results of the .study it can be concluded 1) All basketball extracurricular of State Senior High Schools in kabupaten Purworejo already had extracurricular training programs, only there were a number of schools that still having incomplete extracurricular basketball training programs 2) All facilities have been provided by schools to carry out basketball extracurricular activities, but still there were facilities that were classified as incomplete.